2008
DOI: 10.1128/jvi.00135-08
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Receptor Binding Specificity of Norwalk Virus

Abstract: Noroviruses are positive-sense, single-stranded RNA viruses that cause acute gastroenteritis. They recognize human histo-blood group antigens as receptors in a strain-specific manner. The structures presented here were analyzed in order to elucidate the structural basis for differences in ligand recognition of noroviruses from different genogroups, the prototypic Norwalk virus (NV; GI-1) and VA387 (GII-4), which recognize the same A antigen but differ in that NV is unable to bind to the B antigen. Two forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
219
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(225 citation statements)
references
References 19 publications
4
219
2
Order By: Relevance
“…In the P2 domain they found two class-specific surface patches, indicating a putative carbohydrate-binding site, one consisting of residues 329, 373, 375 and 377 and the other consisting of residues 306 and 310 (Norwalk numbering) (Chakravarty et al, 2005). Recently, Bu and coworkers confirmed by mutational analysis the importance of residues 329 and 377 in binding of Norwalk Pparticles to the A trisaccharide (Bu et al, 2008). Similarly, we found residues 329 (Glu), 373 (Pro) and 377 (Ser) ACR in all partitions, while residue 375 was class-specific from partition I to V, and ACR (Leu) from partition VI to X.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the P2 domain they found two class-specific surface patches, indicating a putative carbohydrate-binding site, one consisting of residues 329, 373, 375 and 377 and the other consisting of residues 306 and 310 (Norwalk numbering) (Chakravarty et al, 2005). Recently, Bu and coworkers confirmed by mutational analysis the importance of residues 329 and 377 in binding of Norwalk Pparticles to the A trisaccharide (Bu et al, 2008). Similarly, we found residues 329 (Glu), 373 (Pro) and 377 (Ser) ACR in all partitions, while residue 375 was class-specific from partition I to V, and ACR (Leu) from partition VI to X.…”
Section: Discussionsupporting
confidence: 56%
“…However, it is important to remark that the virus investigated in this study belongs to genogroup II.3, and may therefore have different or additional binding pattern as compared with the VA387 (GII.4) and Norwalk virus (GI.I) strains (Tan & Jiang, 2005). Indeed, Bu and coworkers recently showed that, although Norwalk and VA387 strain (both bind A and H antigens in related regions within the P2 domain) have similar binding patterns, the interaction with the receptor includes different amino acids (Bu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…HBGAs are complex carbohydrates present on mucosal epithelial cells or free antigens in blood, saliva, and other fluids (32). X-ray crystal structures of norovirus P domains in complex with different HBGAs have defined distinct binding sites for GI and GII viruses (8,11,12,21); in particular, the HBGA binding site of GII is located at the dimeric interface of two P domains, whereas the HBGA binding site in GI is located within a single P domain (8,11,12,21).A number of recent studies have shown that natural fruits or their constituents, including orange juice, pomegranate juice, cranberry juice, and grape seed extract, can inhibit and/or reduce feline calicivirus and murine norovirus infectivity (23,(48)(49)(50)54). Although there have been no studies to support the idea that natural fruits or their constituents can prevent human norovirus infections, and data on the mode of inhibition of fruits have been lacking, the stability of human norovirus virus-like particles over a pH range of 3 to 7 (3) suggested that the effect might be related to a specific interaction with compounds in fruits rather than a pH effect.…”
mentioning
confidence: 99%
“…The VP1 is the major structural protein of norovirus and its P2 subdomain, which is located at the outmost surface of the viral capsid, comprises the binding surface for HBGA (Bu et al, 2008;Cao et al, 2007;Choi et al, 2008;Tan et al, 2003). The function of VP2 is currently undefined and there is not sufficient information to address this minor protein as an antiviral target.…”
Section: Targeting Structural Proteins Of Norovirusmentioning
confidence: 99%
“…Genomic and subgenomic RNA of norovirus with the genome linked protein VPg at the 5' end and the poly(A) tail at 3' end is shown along with the nonstructural proteins (NS1-7) encoded by ORF1 as well as the structural proteins (VP1 and VP2), encoded by ORF2 and 3. See text for further details the outmost surface of the viral capsid and comprises a hypervariable region, where resides the binding interface for HBGA association with norovirus (Bu et al, 2008;Cao et al, 2007;Choi et al, 2008;Tan et al, 2003). The VP2 is a small, basic structural protein encoded by the ORF3 which is present in one or two copies per virion (Glass et al, 2000;Hardy, 2005).…”
Section: Classification and Genome Organizationmentioning
confidence: 99%